(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
This study aims to examine the psychometric properties of the short version of Attitudes Toward Lesbians and Gay Men Scale (ATLG) translated in Macedonian language. A total of 500 undergraduate students who study 5 different disciplenes (Medicine, Stomatology, Psychology, Special education and rehabilitation and Social work) participated voluntarily by providing answers to several questionnaires: the target instrument (ATLG-S) Transphobia Scale (TS)), Eight Item Empathy Quotient test, the short version of the Scale of Dominance Orientation (SDO) and the short version of Trust scale. The analysis of data suggest that the internal consistency of the ATLG-S is acceptable, both for the whole instrument (α=.90) and for the lesbian (α=.84) and gay subscales (α=.74). In addition, the principal components analyses followed by oblimin rotation extracted a two-factor solution of the instrument internal structure. Although not in line with the previous findings, this structure might be explained and considered as adequate. The known-groups, convergent and divergent validity examination have confirmed that the ATLG Scale is a valid and reliable measure of homonegativity and strongly support its use as a research instrument among students and practitioners in the helping professions.